Discovery of Heterocyclic Analogs of Diaminopimelic Acid as Promising Antibacterial Agents Through Enzyme Targeted Inhibition of Lysine Biosynthesis - Shaikh, Mohd S.; Kale, Mayura A.; Sharuk, Khan (Current Enzyme Inhibition, 2018)
Introduction: Peptidoglycan, key constituent of bacterial cell wall, presents a novel target for broad spectrum antibiotics and extensive research is being conducted to synthesize inhibitors of its biosynthesis. A majority of bacteria need either lysine, or meso-DAP, as component of peptidoglycan. Background: Present compound has been designed as per structure activity relationship (SAR) of reported analogues and enzyme active site studies. The compounds have been subjected to in silico studies by PASS which confirm them to act as inhibitors of dapB, dapF, dapA and ddh. In this work, we have successfully synthesized various analogues of meso-DAP as per SAR requirement. The carboxyl groups in DAP were effectively replaced with five membered heterocyclic moieties and central carbon atom was replaced with sulfur. Compounds 4 and 5 were tested for antibacterial activity as per the inferences of predicted hypothesis to inhibit DAP enzymes. Methods: Antibacterial evaluation was performed on gram-positive and gram-negative bacteria. Two selectively protected tetrazole and imidazole analogues of DAP viz., compounds 4 and 5 were synthesized by condensation of NBS as brominating agent and later on, N-Trityl protected five member heterocycles obtained showed expected mono-bromide 17 and 11. This further allowed reaction of these heterocycles with thiol group of cystiene, thus making them susceptible to oxidation in the presence of K2CO3 to yield N-Trityl protected analogues 18 and 12. The separation and hydrolytic deprotection of 18 and 12 shows sterically hindered pure 5 and 4. Protein-ligand interaction was investigated for hydrophobic/ hydrophilic properties of these complexes and docking was carried out by VLife MDS 4.2 based on scoring functions. Results: A computational ligand-target docking approach was used to analyze structural complexes of dapF (target) with 4, 5 and LL-DAP (ligand) in order to understand the structural basis of this protein target specificity. The energy of interaction of compounds 4 and 5 with the dapF is assigned “grid point.” At each step of the simulation, the energy of interaction of ligand and protein was evaluated using atomic affinity potentials computed on a grid. The minimum binding energy indicated that dapF was successfully docked with compounds 4 and 5 showing good affinities. Both analogs showed relatively greater binding affinity as compared to natural substrate LL-DAP which showed minimum binding energy. Conclusion: In the present research, the compounds 4 and 5 have been designed such that they would be acting as inhibitors of enzymes involved in lysine pathway. Also, the results of antibacterial activity have revealed that these compounds can serve as good drug candidates against bacterial infections.
Keywords: diaminopimelic acid